Saffron Republic: Hindu Nationalism and State Power in India, Thomas Blom Hansen & Srirupa Roy - Fatima Azhar (CISS Insight Journal, 2024)
“Saffron Republic: Hindu Nationalism and State Power in India,” edited by Thomas Blom Hansen and Srirupa Roy, explores the phenomenon and evolution of the “New Hindutva” practiced by the Bharatiya Janata Party (BJP) after assuming power in India in 2014. The book traces the evolution of Hindu nationalism from a movement characterized by mass mobilization in the 1980s and 1990s to a well-rounded political ideology, focusing on transforming India’s cultural and religious identity and foreign and economic policies. As Hindu nationalism becomes prevalently ubiquitous in statecraft and governance, this collection of essays examines how Hindutva has become deeply rooted in the socio-political foundations of India, to the extent that the once stark dichotomy between secular Indian democracy and Hindu nationalism has disappeared. This volume describes contemporary Hindutva as democratic authoritarianism or authoritarian populism.